2021
DOI: 10.3390/microorganisms10010040
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effect of Ozone on Pathogenic Bacteria

Abstract: (1) Background: Disinfection of medical devices designed for clinical use associated or not with the growing area of tissue engineering is an urgent need. However, traditional disinfection methods are not always suitable for some biomaterials, especially those sensitive to chemical, thermal, or radiation. Therefore, the objective of this study was to evaluate the minimal concentration of ozone gas (O3) necessary to control and kill a set of sensitive or multi-resistant Gram-positive and Gram-negative bacteria.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 105 publications
2
20
0
Order By: Relevance
“…Conversely, when we investigated its metabolic capacity through resazurin, we found a significant reduction in values only for two strains, showing that ozone was able to interfere with cell viability of S. aureus (MRSA), which showed inhibition of about 99.6%, followed by P. aeruginosa XDR (29.2%). Curiously, in a recent study using the same strains, we have shown that ozone at low concentrations did not interfere with bacterial growth, but it could significantly inhibit cell viability [102]. Interestingly, reference strains (ATCC) from all species were less susceptible to ozone treatment.…”
Section: Discussionmentioning
confidence: 78%
“…Conversely, when we investigated its metabolic capacity through resazurin, we found a significant reduction in values only for two strains, showing that ozone was able to interfere with cell viability of S. aureus (MRSA), which showed inhibition of about 99.6%, followed by P. aeruginosa XDR (29.2%). Curiously, in a recent study using the same strains, we have shown that ozone at low concentrations did not interfere with bacterial growth, but it could significantly inhibit cell viability [102]. Interestingly, reference strains (ATCC) from all species were less susceptible to ozone treatment.…”
Section: Discussionmentioning
confidence: 78%
“…This difference might be due to thicker layer of peptidoglycan, which provides physical strength to the bacterial cell wall, in Gram-positive Cmm than Gram-negative Pst . Several other reports also demonstrated that Gram-negative bacteria are more sensitive O 3 than Gram-positive ones ( Restaino et al, 1995 , Moore et al, 2000 , Zuma et al, 2009 , Rangel et al, 2022 ). Similarly, the fact that O 3 in gaseous form did not show any effect against fungal pathogens Fol and Forl in non-soaked tomato seeds at the tested duration and concentration may be due to the thicker cell wall structure of the fungi.…”
Section: Discussionmentioning
confidence: 79%
“…Conversely, when we investigated its metabolic capacity through resazurin, we found a significant reduction in values only for two strains, showing that ozone was able to interfere with the cell viability of S. aureus (MRSA), which showed inhibition of about 99.6%, followed by P. aeruginosa XDR (29.2%). Curiously, in a recent study using the same strains, we showed that ozone at low concentrations did not interfere with bacterial growth, but it could significantly inhibit cell viability [51]. Interestingly, all species' reference strains (ATCC) were less susceptible to ozone treatment.…”
Section: Discussionmentioning
confidence: 79%
“…For example, ozone gas in the concentration of 25 ppm caused a significant reduction in the number of viable bacteria and the total biomass of K. pneumoniae biofilm [48]. Furthermore, ozone seems to be very effective against planktonic bacteria, which are susceptible to ozone action and are often significantly reduced or completely eradicated from the surfaces with smaller concentrations [49][50][51][52]. Currently, with the COVID-19 pandemic, ozone has been investigated as a possible preventive measure for the spread of infection [53], in hospital hy-giene for disinfecting rooms [54], in viability on different surfaces [55], and as a therapeutic option in the treatment of patients [24,56].…”
Section: Introductionmentioning
confidence: 99%